Comportamento mecânico de materiais compósitos submetidos a impacto de baixa velocidade na presença de concentradores de tensão - Neto, José Lira Braga (2020)
Composites have been widely used in various engineering sectors due to specific high strength and high specific modulus. With the increasing application of composites, it is increasingly important to understand, predict and control their flaws in which defects can play a key role. Defects are imperfections of materials generated in manufacturing or during prolonged service. One of the most common defects in composite processing refers to the formation of voids. Voids cause the reduction of mechanical properties and therefore it is important to evaluate the behavior of the material in the presence of this type of defect. Another factor that can lead to a reduction in properties is the damage caused by low-speed impacts, generating internal damage to the material compromising its integrity. This work aims to evaluate the behavior due to the low velocity impact on polymeric composites considering stress concentrators (two side holes at the point of impact) and find the residual mechanical properties of these materials through fai (Flexural After Impact). In the analysis of residual properties, the effects of damage and stress concentrators will be dismembered by evaluating their individual influences on the increase of the stress concentration factor (K). This dismemberment will be carried out through tests considering the isolated effects of each case and a formulation that relates them. In addition, it will also evaluate the influence of the percentage of voids on impact and residual resistance by developing two composites based on fiberglass-E fabric with different void percentages. From the tests performed, it was found that the damage caused by the impact increased by 18% the concentration factor of the material, but in the samples tested with lateral holes the damage had an influence of only 5% in the reduction of the residual resistance